Behaviour of a Space Inverted Triangular Steel Truss - Andrejs Podkoritovs; Dmitrijs Serdjuks; Vadims Goremikins; Karina Buka-Vaivade; Mikhail Nikolaevich Kirsanov (The Baltic Journal of Road and Bridge Engineering)
Behaviour of the inverted triangular truss, which is widely used as a bridge girder, was investigated analytically and experimentally. Cold-formed square hollow cross-sections of steel grade S355J2H with dimensions 80 mm × 4 mm, 90 mm × 4 mm and 40 mm × 4 mm were selected for the top and bottom chords and bracing elements of the truss with 12.56 m span, correspondingly. Five FEM models were developed using software Dlubal RFEM. The main specific feature of the models is the difference in modelling of joint behaviour considering plastic behaviour and stiffness of truss connections. It was shown that the FE model of the truss where the members were modelled by the truss type finite elements and the joints modelled by the shell type ones allows predicting behaviour of the truss with precision of up to 3.9%. It was shown that precision of the suggested FEM model grows 4.36 to 4.62 times in comparison with the traditional FEM models where the members were modelled by the truss finite elements with the pinned and rigid joints in case of plastic joint behaviour. Precision of the suggested FEM model is identical to that of the traditional FEM models regarding the case of elastic joint behaviour.